2013
DOI: 10.4028/www.scientific.net/amm.397-400.205
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Energy Separation Effect in Vortex Tube for Natural Gases

Abstract: This paper aims to investigate fixed composition natural gases including N2, CH4 and C2H4 energy separation effect in vortex tube. Energy separation phenomena of those gases were investigated by means of three-dimensional Computational Fluid Dynamics (CFD) method. Flow fields of natural gases in fixed inlet boundary conditions were simulated. The results main factors were found that affect the energy separation with cold mass fraction being 0.7 and pressure drop ratio being 3.90. At the same time, this paper h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…They demonstrated that certain working gas properties, including inlet pressure, specific heat ratio, and thermal conductivity, play a significant role in energy separation in vortex tubes. Wang et al investigated the energy separation performance of different gases in a vortex tube using computational fluid dynamics; their approach was focused on the number of atoms contained in the gas molecules. Their results indicated that an enhanced temperature separation effect was observed for gas molecules that had low specific heat capacities and contained only one or two atoms.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that certain working gas properties, including inlet pressure, specific heat ratio, and thermal conductivity, play a significant role in energy separation in vortex tubes. Wang et al investigated the energy separation performance of different gases in a vortex tube using computational fluid dynamics; their approach was focused on the number of atoms contained in the gas molecules. Their results indicated that an enhanced temperature separation effect was observed for gas molecules that had low specific heat capacities and contained only one or two atoms.…”
Section: Introductionmentioning
confidence: 99%